Pengaruh Nation Branding â€œPesona Indonesiaâ€ Terhadap Minat Berkunjung Wisatawan Nusantara (Survei Pada Pengikut Instagram @pesonaid_travel) - Edithania, Regina Oktaria (Manajemen Bisnis Kompetensi, 2018)
This research is motivated by many countries, especially in Asia region, which apply nation branding to promote tourism. The tight competition makes the Ministry of Tourism of the Republic of Indonesia proclaims nation branding â€œPesona Indonesiaâ€ to attract the interest of domestic tourists to explore in their own country. Departing from this phenomenon, this study aims to determine whether or not the influence of nation branding on the interest of tourists visiting the archipelago. This research uses quantitative and explanative approach to test the correlation between variables. The method used is survey by distributing questionnaires to 416 respondents with simple random sampling technique. Hypothesis testing shows empirical evidence that a nation branding significant positive effect on interest in visit intention. The dimension of culture heritage contributes the greatest influence of the nation branding on the visit intention.Keywords: nation branding, visit intention, pesona indonesia